2014
DOI: 10.1080/21551197.2014.959680
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Medication Adherence in Low-Income Older Medicare Beneficiaries With Type 2 Diabetes

Abstract: Little is known about diabetes management among low-income older Americans. This study used statewide self-administered survey and Medicare claims data to examine the relationships of food insecurity and medication (re)fill adherence in a sample of Medicare Part D beneficiaries with type 2 diabetes in need of food assistance in Georgia in 2008 (n = 243, mean age 74.2 ± 7.8 years, 27.2% African American, 77.4% female). (Re)fill adherence to oral hypoglycemics was measured as Proportion of Days Covered. Food ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…This study, which was restricted to adults with chronic diseases, found that people living in food-insecure households were more likely to report CRMU. Similar findings have been demonstrated from smaller studies in different parts of the country among the non-elderly (25)(26)(27)(28)(29) and among low-income older adults (30)(31)(32).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This study, which was restricted to adults with chronic diseases, found that people living in food-insecure households were more likely to report CRMU. Similar findings have been demonstrated from smaller studies in different parts of the country among the non-elderly (25)(26)(27)(28)(29) and among low-income older adults (30)(31)(32).…”
supporting
confidence: 84%
“…We use the nationally representative National Health Interview Survey, as did Berkowitz and colleagues, but focus on older adults, and we do not limit the analysis to those with chronic diseases (18). Bengle and colleagues (30) and Sattler and colleagues (31,32) also focus on older adults, but their sample is limited to participants of the Older Americans Act Nutrition Program (receiving delivered meals or congregate meals) or those on a waitlist for services in Georgia. The association between FI and CRMU among older adults who sought out or were referred to nutrition assistance programs may differ from the general population of older adults.…”
mentioning
confidence: 99%
“…[49] One article was irretrievable for full-text review and was excluded. [50] As shown in Figure 1, 25 articles representing 25 studies met criteria and were included in our review. Authors LSM and EB collected the following information from each eligible study: sample description, study design (cross-sectional or longitudinal analysis of disparities) and year(s) data were collected, racial/ethnic disparities assessed, self-care behaviors examined, and whether identified self-care discrepancies were unadjusted, adjusted, or both, and (if applicable) covariates included in adjusted analyses of disparities.…”
Section: Resultsmentioning
confidence: 99%
“…Associations between perceived financial burden and poor glucose control among diabetes patients in outpatient clinics have been observed. 11 Rates of food insecurity are as high as 54% among older adults with diabetes 12 , and those pressures may lead to decreased adherence to diabetes self-care behaviors and worse glycemic control. 13,14,15 Dietary regimens are common therapeutic strategies integral to prevention and effective management of chronic disease, yet also vulnerable to CRN.…”
Section: Introductionmentioning
confidence: 99%